Audit committee composition and auditor reporting: a study in Malaysian environment / Roziani Ali - Ali, Roziani (2001)
In the wake of corporate failures following economic crisis starting in 1997, the role of audit committees as corporate governance mechanism has became more important to regulators, the accounting profession and the business community. A research was conducted by Carcello and Neal (2000) examining the relation between the composition of financially distressed firm's audit committees and the likelihood of receiving going-concern report for the year 1994. Hence, this study is conducted to examine the same relation in Malaysian context by examining published information for the year 1998. While previous study found an inverse relationship between percentage of affiliated directors on audit committee and the likelihood of receiving modified going concern report, this study finds insignificant positive relationship between the variables. The result of the study therefore does not support many parties such as the shareholders and Kuala Lumpur Stock Exchange's concern about financial-reporting quality and the recent calls for more independent audit committee. The study document evidences that the likelihood of receiving a going concern report for financially distressed firms is not significantly affected by the audit committee composition.